2015
DOI: 10.5617/nordina.987
|View full text |Cite
|
Sign up to set email alerts
|

Scientific literacy as social practice: Implications for reading and writing in science classrooms

Abstract: This article provides an introduction to what it means to adopt a view of literacy as social practice for science education. This view of literacy builds on the idea that reading and writing are best regarded as situated social practices involving text, not as a set of decontextualised and universally applicable skills. First, we draw on sociocultural perspectives on literacy to show how these perspectives inform our understanding of literacy when the context is science. Second, we use related research literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
1
11
1
8
Order By: Relevance
“…esim. Buchholz & Pyles, 2018;Norris & Phillips, 2003;Sørvik & Mork, 2015) Eräs useisiin luonnontieteellisen lukutaidon määritelmiin läheisesti liittyvä tavoite on, että tiedeopetuksen tulisi olla relevanttia -eli hyödyl-listä tai kiinnostavaa (vrt. Stuckey, Hofstein, Mamlok-Naaman, & Eilks, 2013) -niillekin oppilaille, jotka eivät tähtää luonnontieteellisille aloille.…”
Section: Johdantounclassified
See 1 more Smart Citation
“…esim. Buchholz & Pyles, 2018;Norris & Phillips, 2003;Sørvik & Mork, 2015) Eräs useisiin luonnontieteellisen lukutaidon määritelmiin läheisesti liittyvä tavoite on, että tiedeopetuksen tulisi olla relevanttia -eli hyödyl-listä tai kiinnostavaa (vrt. Stuckey, Hofstein, Mamlok-Naaman, & Eilks, 2013) -niillekin oppilaille, jotka eivät tähtää luonnontieteellisille aloille.…”
Section: Johdantounclassified
“…Lukutaito sen kirjaimellisessa merkityksessä tuo luonnontieteellisen lukutaidon käsitteen lähelle monilukutaidon käsitettä. Näitä käsitteitä ei tyypillisesti ole käsitelty rinnakkain, mutta toisinaan luonnontieteellinen lukutaito on rinnastettu monilukutaidon kanssa tai nähty monilukutaidon eräänä osana (Lavonen ym., 2010;Sørvik & Mork, 2015). Itse asiassa Norris ja Phillips (2003) tekevät eksplisiittisesti eron luonnontieteellisen lukutaidon ja perinteisen lukutaidon välille, sillä heidän mukaansa edellinen eroaa jälkimmäisestä substantiaalisen sisältönsä vuoksi.…”
Section: Luonnontieteellisen Lukutaidon Määritelmätunclassified
“…Historically, emphasis on the actual use of texts in science education has been limited, but a broader view on literacy and a concern for students’ literacy practices is emerging in contemporary research (Blikstad‐Balas & Sørvik, ; Howes et al., ; Norris & Phillips, ; Osborne, , ; Sørvik et al. ; Sørvik & Mork, ). Sørvik and Mork (, p. 276) explained how a social view of literacy “provides science education with the theoretical perspectives to examine the role of literacy in a transcending science subject.” As they emphasized, a theoretical perception of reading and writing as situated within a social context, enables researchers to “consider how literacy is a part of contexts that influence science education and are relevant to the long‐term goal of scientific literacy” (Sørvik & Mork, , p. 276).…”
Section: Theoretical Perspectives: Writing As a Social Practicementioning
confidence: 99%
“…Texts and socially meaningful ways of using them are essential parts of science (Knorr‐Cetina, ; Norris & Phillips, ; Osborne, ; Sørvik & Mork, ). Research has demonstrated that professional researchers and scientists engage in a variety of textual activities not only for documenting their research and presenting it to peers in a number of ways but also for reading, discussing, and commenting on others’ research.…”
Section: Introductionmentioning
confidence: 99%
“…We use the term scientific literacy in a functional sense, meaning that scientific literacy enables participation in science discourses (Knain, 2015;Sørvik & Mork, 2015). Roberts (2007Roberts ( , 2011 outlines what he calls different 'visions' of the purposes for learning school science: Vision I and Vision II.…”
Section: Scientific Literacymentioning
confidence: 99%